A new species of palicid crab (Crustacea, Decapoda: Brachyura: Palicidae) from the Andaman Sea, west coast of Thailand - Promdam, Rueangrit; Nabhitabhata, Jaruwat (Zootaxa, 2012)
Pseudopalicus bidens (Brachyura, Palicidae) is described as a new species from the Andaman Sea, on the western coast of Thailand. The new species can be distinguished from its congeners by its anterolateral teeth on each side of the carapace, with the first two being considerably larger than the last two, as well as for morphology of the gonopods. The new species will bring the number of described Pseudopalicus Moosa & Serene, 1981, species to twelve.